Potensi dan Efektivitas Limbah Cair Industri Tahu Sebagai Pupuk Organik Cair Terhadap Pertumbuhan Cabai dan Tomat - Shinta Ajeng Salyndri Hifdzul Aqlys; Okik Hendriyanto Cahyonugroho (Jurnal Serambi Engineering, 2024)
Most of the tofu industries in Jombang dump their waste directly into the river. This causes discolourationof the river and unpleasant odours. High organic content in the water can reduce dissolved oxygen (DO)levels and increase pollutant parameters that can harm the environment. Waste recycling can be a way toreduce pollution. With a high organic content, tofu liquid waste has great potential as a fertiliser. Theaddition of EM4 bioactivator in the production of fertiliser can help the fermentation process with the aimof improving the quality of soil structure. This study aims to determine the potential and effectiveness ofliquid organic fertilizer produced from tofu liquid waste. The research method used was a field experimentwith a quantitative approach. The experiment starts with the production of liquid organic fertilizer fromtofu liquid waste, which is then applied to chilli (Capsicum frutescens L) and tomato (Solanumlycopersicum L) plants, and there is a control (no treatment or fertilizer) for comparison. The observationresults show that the liquid organic fertilizer (POC) from tofu liquid waste is very influential on the growthof chilli and tomato, especially in the vegetative period.